Role changes in software development projects using agile methodologies: A case study of private companies in Guatemala City - Santos-Tiberio, Hector (2022)
This new era of software development began to generate changes in the way software development teams are organized, new roles and functions are established in project management. In many cases this role does not exist and a similar role must be chosen and the project manager must adapt. This research seeks to know the changes made by software project managers in private companies in Guatemala City. The research hypothesizes that the implementation of agile methodologies produces an update in the functions and roles in the area of project management in private institutions. For this purpose, a four-phase study was carried out: Design of the instrument, Distribution of the instrument, Processing of the information and Analysis of the information. A sample of 35 private companies was worked with the participation of software development team leaders. The results obtained from an online survey allowed us to discover that there are considerable changes in the roles and responsibilities of project leaders in organizations that migrate from traditional methodology to agile methodology.